2016
DOI: 10.1080/17597269.2016.1224290
|View full text |Cite
|
Sign up to set email alerts
|

Biofuel production: tapping into microalgae despite challenges

Abstract: 8Biofuels provided 2.7% of world's transportation fuel in 2015 which is expected to go up to 9 28% by 2050. However, most of the biofuel produced till date is from crops that can be used 10 as food or feed. Microalgae or most famously the 3 rd generation of biomass has the potential 11to overcome the problems associated with this food vs fuel debate. Microalgae are microscopic 12 photosynthetic organisms which have the ability to fix CO2. Thermochemical conversion via 13 hydrothermal liquefaction is a favourab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 75 publications
0
7
0
Order By: Relevance
“…Synthetic biologists have been successful in assembling genetic material and manipulating the lipid content of microalgae, as well as maximizing biomass accumulation and biofuel yield (Jagadevan et al, 2018). These results are promising for the biofuels industry from the microalgal perspective (Randhawa et al, 2017). In the context of microalgae, the alteration of lipid iScience Article biosynthesis pathways through the induction of a stress response to a change in environment (such as temperature, nutrient limitation, salinity) is a common practice to enhance the production of target compounds, including those that are used to produce workable biofuels (Rawat et al, 2013).…”
Section: Multi-omic Data Integration In Microalgaementioning
confidence: 99%
See 2 more Smart Citations
“…Synthetic biologists have been successful in assembling genetic material and manipulating the lipid content of microalgae, as well as maximizing biomass accumulation and biofuel yield (Jagadevan et al, 2018). These results are promising for the biofuels industry from the microalgal perspective (Randhawa et al, 2017). In the context of microalgae, the alteration of lipid iScience Article biosynthesis pathways through the induction of a stress response to a change in environment (such as temperature, nutrient limitation, salinity) is a common practice to enhance the production of target compounds, including those that are used to produce workable biofuels (Rawat et al, 2013).…”
Section: Multi-omic Data Integration In Microalgaementioning
confidence: 99%
“…Through the understanding of transcription levels and gene activation data gathered from transcriptomics, the effectiveness of genetic alterations can be measured as previously achieved for other organisms, allowing for optimization of the target product. For example, if the new gene insert is operating at its optimum, the transcriptomic data should show an increase in the mRNA of the target gene when compared with the wild type (Randhawa et al, 2017). Based on genomic and transcriptomic data, Wang et al (2019) recently identified a series of neutral sites on the chromosome of Synechococcus sp.…”
Section: Multi-omic Data Integration In Microalgaementioning
confidence: 99%
See 1 more Smart Citation
“…The study concluded that the outdoor culturing of GM microalgae fails to affect the microalgal diversity in the native ecosystem. However, before drawing any conclusion, extensive studies should be conducted as it is evident that regulatory certainty would be critical in the development of economically viable processes for algaebased biofuel production (Glass, 2015;Randhawa et al, 2017). Recent success in technology demonstration of biojet fuel is a sign of emerging prospects of microalgal biofuel for commercial ignition (Siobhan, 2010;Gyekye, 2017;Chandra, 2018).…”
Section: Challenges and Future Prospectsmentioning
confidence: 99%
“…Alternatively, the availability of more than 20 whole algal genomes and recent developments in molecular toolboxes allows for (targeted) genetic engineering strategies to improve (lipid) metabolism (Hamed, 2016;Radakovits et al, 2010;Randhawa et al, 2017). Although many attempts were made, only a few studies resulted in strains with improved TAG productivities (Table 6.1).…”
Section: Classical Strain Improvementmentioning
confidence: 99%